Exploring Social Actions: A Study of Children's Social Actions and Children's Novels as Learning Tools - Susanto, Rudi Umar; Suyatno; Darni (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
The narrative of children's thoughts in children's novels plays an important role in shaping children's understanding of their social environment. Through social action narratives, children are actively involved in internalizing social norms and values, as well as current phenomena so that they can become a means of learning in the future. Based on this background, the focus of this research is the form of children's social action narratives in children's novels. This research uses an interpretative qualitative approach with a parallel reading approach. This method describes and interprets the narrative of children's social thinking in children's novels. Therefore, the data sources for this research are a novel entitled